Application of Failure Mode and Effects Analysis (FMEA) to Improve Medical Device Reliability - F.H.P.A, Dattu; Syed Tarmizi, Syed Shazali; S. J., Tanjong; Abdul Rani Achmed, Abdullah (Kiban Multidisciplinary Business Management Welfare Society, 2024)
Medication safety is a pressing global concern, highlighting the need for reliable and secure medical devices within the healthcare industry. Device malfunctions can severely affect patient well-being, necessitating effective engineering and maintenance practices to address these risks. This research constitutes a significant advancement in this field by utilizing Failure Modes and Effects Analysis (FMEA) to evaluate and improve the dependability and safety of medical devices. The study prioritizes risks and formulates targeted mitigation strategies by systematically identifying potential failure modes, assessing their consequences, and determining their likelihood of occurrence and detection. The comprehensive FMEA process examines operational conditions and identifies critical areas for enhancement, resulting in substantial improvements in device reliability. The findings emphasize the importance of proactive risk management and continuous improvement in the engineering and maintenance of medical devices. This paper provides a solid foundation for implementing FMEA in engineering and maintaining medical devices, offering valuable insights for manufacturers and regulatory agencies to enhance device safety and performance.